A gestão de serviços e stakeholders nos domínios da hospitalidade: um estudo de casos nas padarias do bairro Jardins - FERNANDES, Vinícius Val Gonçalves Cordeiro (2015)
The article proposes an analysis of the management services and stakeholders in the bakery of the Jardins district, considering the co-creation of value and influence of the areas of hospitality in social relations that exist there. The overall objective was to understand the influence of the areas of hospitality in relations between bakeries and stakeholders. Starting from this issue the following propositions were established: good relationships with stakeholders, always favors the co-creation of values and the formulation of a strategy that meets the expectations of all; the co-creation occurs, even if all the stakeholders involved, have a good relationship; the researched object has prioritized the product offering, not focusing on the experience offered to customers, thus bypassing the process of co-creation. Interviews were conducted with managers and employees follow a script. Through this research it was possible to identify the areas of hospitality facilitate the implementation of co-creation processes and there is a concern with the service and customer experience by bakeries, albeit disorganized and intuitive way